Leadership Style of Local Actors in Community Development and Empowerment - Ery Purwanti; Dwiningtyas Padmaningrum; LV Ratna Devi Sakuntala (Indonesian Journal of Social Responsibility Review (IJSRR), 2023)
Introduction: Tambi Village is one of the villages in Kejajar District which has a high disaster vulnerability index, high landslide vulnerability, high disaster capacity index, and high landslide capacity with a relatively wide area (BPBD Wonosobo, 2018). Starting from concern about such conditions, one of the residents of Tambi Village moved to innovate in agriculture by planting coffee plants on barren land. Most community plants grow horticultural crops that cannot store water and cannot grow properly with the presence of protective plants in the vicinity, so they are prone to landslides during the rainy season. The main purpose of coffee cultivation is to preserve nature and increase the welfare of the community with the coffee yield. The purpose of the study: to determine the leadership/role of Mr. Romadhon as a local actor in developing and empowering the Tambi Village community. Methods: descriptive research with interviews and literature study conducted in Tambi Village, by determining the information provider by purposive or judgmental sampling. Research time 15 June 2022. Data collection by interview, observation, and documentation. Results: the role of local actors in community empowerment is very significant and their roles: (1) Initiate (initiator), (2) Provide motivation (motivator), (3) Coordinate (coordinator), (4) Make plans (planner), (5) Carry out facilitation (Facilitator), and (6) Conduct communication and relations (Communicator), (7) Provide education (Educator) and (8) As a deliberation (Negotiator). Conclusion: leadership/role of local actors in empowering the Tambi Village community as initiator, motivator, coordinator, planner, facilitator, communicator, educator,  and negotiator.